2017
DOI: 10.1111/medu.13386
|View full text |Cite
|
Sign up to set email alerts
|

Back from basics: integration of science and practice in medical education

Abstract: Context In 1988, the Edinburgh Declaration challenged medical teachers, curriculum designers and leaders to make an organised effort to change medical education for the better. Among a series of recommendations was a call to integrate training in science and clinical practice across a breadth of clinical contexts. The aim was to create physicians who could serve the needs of all people and provide care in a multitude of contexts. In the years since, in the numerous efforts towards integration, new models of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…The other useful lesson is that mechanistic understanding in medicine does not need to be constrained to traditional basic science content domains. While it is often taken for granted that there are biochemical, anatomical, and physiological explanations for clinical signs and symptoms, virtually any form of knowledge that creates explanatory links within a network can have value in clinical judgement . Work by Lucey has identified “new basic and clinical sciences” that extend beyond the traditional formulations of relevant knowledge in medicine .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other useful lesson is that mechanistic understanding in medicine does not need to be constrained to traditional basic science content domains. While it is often taken for granted that there are biochemical, anatomical, and physiological explanations for clinical signs and symptoms, virtually any form of knowledge that creates explanatory links within a network can have value in clinical judgement . Work by Lucey has identified “new basic and clinical sciences” that extend beyond the traditional formulations of relevant knowledge in medicine .…”
Section: Introductionmentioning
confidence: 99%
“…While it is often taken for granted that there are biochemical, anatomical, and physiological explanations for clinical signs and symptoms, virtually any form of knowledge that creates explanatory links within a network can have value in clinical judgement. 32 Work by Lucey has identified "new basic and clinical sciences" that extend beyond the traditional formulations of relevant knowledge in medicine. 33 Behavioural sciences such as psychology and economics can be used alongside biomedical sciences to form the critical conceptual understanding needed for clinical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, since the common curricular pattern in health professions education generally emphasizes didactic basic science education in the early years and patient care-based clinical education in the latter years, Bandiera et al noted that integration of basic and clinical sciences requires intentional efort. 21,22 The revision of the didactic medical curriculum away from content-speciic disciplines to a more systems-based model, according to Bandiera et al, attempts to integrate teaching of the basic sciences with clinical practice. As stated by Spencer et al, emphasizing the relevance of basic sciences to clinical practice throughout the curriculum will increase retention of knowledge, thus developing a more competent clinician who is able to luently identify critical links between the two.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted that basic sciences can contribute to clinical reasoning through its connections with clinical knowledge (5,22,23). These links between basic sciences and clinical content should be strong within the minds of individual learners (27,28) for cognitive integration to happen (2). Studies have also reported that cognitive integration of knowledge, which helps in the application of basic science knowledge to clinical contexts, would not happen spontaneously (15,16) just by exposing students to an integrated curriculum (15).…”
Section: Discussionmentioning
confidence: 99%